Temporalités du séjour hôtelier dans la Méditerranée romaine occidentale : des uiatores de passage aux inhabitatores perpetui - Marie-Adeline Le Guennec (Pallas, 2015)
This paper focuses on the meaning of time in Roman commercial practices and concepts through an analysis of the particular issue of commercial accommodation in the Roman Western Mediterranean. Two juridical fragments are closely examined and compared with a number of other sources. This comparison sheds light on the significant role played by time in establishing a classification of commercial sojourns during the Roman period. A key distinction can be made between lodgers living in inns on a long-term basis, and travellers staying on the premises for short periods of time for whom commercial accommodation was, per se, temporary. Despite the diversity in accommodation provision practices apparent in the evidence, the idea of a more temporary stay remains central to commercial and cultural norms pertaining to commercial hospitality in the Roman Western Mediterranean; alternative recourse to the type of accommodation that inns provided tends to be marginalised.